High success and low mortality rates with non-invasive ventilation in influenza A H1N1 patients in a tertiary hospital - Timenetsky, Karina T (BioMed Central, 2011)
BACKGROUND: In 2009, an outbreak of respiratory illness caused by influenza A H1N1 virus occurred worldwide. Some patients required Intensive Care Unit (ICU) admission. The use of non-invasive ventilation (NIV) in these patients is controversial, as the aerosol dispersion may contaminate the environment and health-care co-workers. METHODS: Describe the respiratory profile, the mortality rate, and the benefit of using NIV in patients with confirmed diagnosis of influenza AH1N1 who were admitted in the ICU during the year 2009. RESULTS: A total of 1, 401 cases of influenza A H1N1 were confirmed in our hospital by real-time RT-PCR in 2009, and 20 patients were admitted to the ICU. The patients' ages ranged from 18 to 74 years (median of 42). Acute Respiratory Failure (ARF) was present in 70% of patients. The median Acute Physiology and Chronic Health Evaluation II score was 7 (range 7 to 25). Of the 14 patients who developed ARF, 85.7% needed NIV and 14% needed invasive MV at admission. Our success rate (41.6%) with NIV was higher than that described by others. The hospital mortality rate was 2.1%. When influenza A H1N1 arrived in Brazil, the disease was already on endemic alert in other countries. The population was already aware of the symptoms and the health-care system of the treatment. This allowed patients to be properly and promptly treated for influenza A H1N1, while health-care workers took protective measures to avoid contamination. CONCLUSION: In our study we found a high success and low mortality rates with non-invasive ventilation in patients with influenza A H1N1.